Ligand-Activated Peroxisome Proliferator-Activated Receptor β/δ Facilitates Cell Proliferation in Human Cholesteatoma Keratinocytes - Chen Zhang; Yang-Wenyi Liu; Zhangcai Chi; Bing Chen (PPAR Research)
Cholesteatoma is characterized by both the overgrowth of hyperkeratinized squamous epithelium and bone erosion. However, the exact mechanism underlying the hyperproliferative ability of cholesteatoma remains unknown. In this study, we investigated PPAR β/δ expression in human surgical specimens of cholesteatoma and analyzed its functional role as a regulator of epithelial keratinocyte hyperproliferation. We found that the expression of PPAR β/δ was significantly upregulated in cholesteatoma and ligand-activated PPAR β/δ markedly promoted the proliferation of cholesteatoma keratinocytes. Furthermore, we showed that PPAR β/δ activation increased PDK1 expression and decreased PTEN generation, which led to increased phosphorylation of AKT and GSK3β and increased the expression level of Cyclin D1. Overall, our data suggested that the proliferating effect of PPAR β/δ on the cholesteatoma keratinocytes was mediated by the positive regulation of the PDK1/PTEN/AKT/GSK3β/Cyclin D1 pathway. These findings warranted further investigation of PPAR β/δ as a therapeutic target for recurrent or residual cholesteatoma.